2021
DOI: 10.1152/ajpgi.00065.2021
|View full text |Cite
|
Sign up to set email alerts
|

The gastric conduction system in health and disease: a translational review

Abstract: Gastric peristalsis is critically dependent on an underlying electrical conduction system. Recent years have witnessed substantial progress in clarifying the operations of this system, including its pacemaking units, its cellular architecture, and slow wave propagation patterns. Advanced techniques have been developed for assessing its functions at high spatiotemporal resolutions. This review synthesizes and evaluates this progress, with a focus on human and translational physiology. A current conception of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 186 publications
2
81
0
Order By: Relevance
“…Multiple studies have identified ICC network depletion as a pathological hallmark of both gastroparesis, and more recently CNVS, associated with a macrophage-driven immune dysregulation. 11,1619 ICC loss leads to slow-wave irregularities and contractile dysfunction, 16,17,20 which is consistent with our data showing weak, irregular and unstable gastric myoelectrical activity and impaired meal responses. Benchmark studies have shown that ICC depletion is restricted to ∼50% of NVS patients, with the remainder showing normal ICC counts, 16,19 approximating our two subgroups.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Multiple studies have identified ICC network depletion as a pathological hallmark of both gastroparesis, and more recently CNVS, associated with a macrophage-driven immune dysregulation. 11,1619 ICC loss leads to slow-wave irregularities and contractile dysfunction, 16,17,20 which is consistent with our data showing weak, irregular and unstable gastric myoelectrical activity and impaired meal responses. Benchmark studies have shown that ICC depletion is restricted to ∼50% of NVS patients, with the remainder showing normal ICC counts, 16,19 approximating our two subgroups.…”
Section: Discussionsupporting
confidence: 92%
“…Classifications of individual subjects as normal, abnormal or indeterminate tests were therefore undertaken by the consensus panel exclusively according to spectral analyses in this study. The following 3 features were employed, according to the Gastric Alimetry labeling and existing gastric electrophysiology literature: 20,27,52,53 presence of a meal response (power ratio >1.4 compared to a baseline period) presence of a clear and consistent dominant frequency band within the spectral plot presence of a normal rhythm (stability typically within a range of 2.5 - 3.6 cpm) Isolated stable high or low frequencies were not judged abnormal in this study. 16,17,45 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations